Comparison of Depression and Quality of Life Between Patients on Hemodialysis and Their Spouses - Nayereh Baghcheghi; Hamid reza Koohestani (Hamadan University of Medical Sciences, 2020)
Introduction: Patients on hemodialysis and their spouses experience various stresses during illness and dialysis treatment. The aim of this study was to compare depression and quality of life between patients on hemodialysis and their spouses. Methods: An analytical and cross-sectional study was performed using the WHOQOL-Questionnaire tool and Beck Depression Inventory-II to assess the quality of life and the depression, respectively. A total of 172 participants (86 patients undergoing hemodialysis and 86 of their spouses) from two hospitals participated in the study. Results: In total, 89.54% and 91.87% of patients on hemodialysis and their spouses had depression at varying levels (mild to severe), respectively. The mean score of depression in the spouse group was significantly higher than the patients score (P< 0.05). Also, the spouses' score in psychological health domain of the quality of life was significantly lower than the patients' score (P< 0.05). Conclusion: Depression is highly prevalent among patients on hemodialysis and their spouses. Spouses had higher rates of depression and lower quality of life in psychological health domain than patients. Therefore, it is suggested that, like patients, the depression and quality of life of their spouses should be assessed periodically and, if necessary, supportive measures should be taken.